To Register or not to Register? Reflections on Muslim Marriage Practices in Britain - Ali, Shaheen Sardar; Jones, Justin; Shahid, Ayesha (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2021)
This is an abridged version of the article. The full article is available in Jahrbuch für islamische Rechtswissenschaft, edited by Cefli Ademi and Mathias Rohe and published by C.H. Beck/Munich in 2020. The article looks at practices regarding Muslim marriages (nikāhs) in Britain. In Britain, entry on the civil register is required for a Muslim marriage to be recognised as a valid marriage. However, some Muslims do not register their marriage and live in nikāh-only marriages. This article draws upon multiple pieces of research to investigate whether decisions not to register are informed and conscious. This includes surveys, focus group discussions and academic conference panels. The results clearly highlight the plurality and diversity of both Muslim thought and conduct in contemporary Britain, and finds that Muslims are developing a number of ‘new’ Muslim marriage practices, such as taking out a nikāh-only marriage as a means of validating a dating relationship. The article concludes with reflections on possible responses to the considerable challenges in accommodating Muslim and civil laws of marriage.